The Effect of Service Quality on Worth of Mouth Positive Intervening by Student Satisfaction and Attitude, Moderation of Student Characteristics on the Effect of Service Quality on Student Satisfaction - Moch. Saifudin (International Journal of Social Science and Religion (IJSSR), 2021)
This research purpose to analyze affected: 1) service quality to student satisfaction, 2) service quality to student atittudes, 3) moderation of student characteristic at affected service service to student satisfaction, 4) service quality to positive Word of Mouth, 5) student satisfaction to positive Word of Mouth, dan 6) student atittudes to positive Word of Mouth, 7) The mediation of satisfaction and students atittudes on affected of quality service to positive Word of Mouth. The using data was primary data which had by questioner brought to 150 higher students of Economic and Business Islamic Faculty of State Institute for Islamic Studies Purwokerto as respondence. Then, data analized by Structural Equation Modelling (SEM). The result of research shown that: 1) Service quality had positive affected to student satisfaction, 2) Service quality had positive affected to student atittudes, 3) Student characteristic not moderated in affected service quality to student satisfaction, 4) Service quality had positive affected to positive Word of Mouth, 5) Student satisfaction had positive affected to positive Word of Mouth, and 6) Student atittudes had positive affected to positive Word of Mouth, 7) Satisfaction and students atittudes mediating of quality service affect to positive Word of Mouth.